Essential quality parameters of commercial Virgin Coconut Oil - Fabian M. Dayrit; Olivia Erin M. Buenafe; Edward T. Chainani; Ian Mitchelle S. de Vera; Ian Ken D. Dimzon; Estrella G. Gonzales; Jaclyn Elizabeth R. Santos (International Coconut Community, 2007)
Chemical analyses conducted on commercial samples of virgin coconut oil (VCO) produced by four different methods gave the following ranges of values: % Fatty acid composition: C6: 0.24 to 0.49%; C8: 4.15 to 8.30%; C10: 4.27 to 5.75%; C12: 46.0 to 52.6%; C14: 16.0 to 19.7%; C16: 7.65 to 10.1%; C18: 2.86 to 4.63%; C18:1: 5.93 to 8.53%; C18:2: 1.00 to 2.16%; % moisture by Karl Fischer: 0.05 to 0.12%; % matter volatile at 120°C: 0.12 to 0.18%; %free fatty acids as lauric acid: 0.042 to 0.329%; and peroxide value: none detected to 1.40. The tests for % moisture by Karl Fischer and % matter volatile at 120°C can be used to differentiate VCO from and refined, bleached and deodorized coconut oil (RBD CNO). No trans-fatty acid was detected in both VCO and RBD CNO down to 0.01% (w/w) detection limit.